Ancient Adversary – HERV-K (HML-2) in Cancer - Dervan, Eoin; Bhattacharyya, Dibyangana D.; McAuliffe, Jake D.; Khan, Faizan H.; Glynn, Sharon A. (Frontiers in Oncology, 2021)
Human endogenous retroviruses (HERV), ancient integrations of exogenous viruses, make up 8% of our genome. Long thought of as mere vestigial genetic elements, evidence is now accumulating to suggest a potential functional role in numerous pathologies including neurodegenerative diseases, autoimmune disorders, and multiple cancers. The youngest member of this group of transposable elements is HERV-K (HML-2). Like the majority of HERV sequences, significant post-insertional mutations have disarmed HERV-K (HML-2), preventing it from producing infectious viral particles. However, some insertions have retained limited coding capacity, and complete open reading frames for all its constituent proteins can be found throughout the genome. For this reason HERV-K (HML-2) has garnered more attention than its peers. The tight epigenetic control thought to suppress expression in healthy tissue is lost during carcinogenesis. Upregulation of HERV-K (HML-2) derived mRNA and protein has been reported in a variety of solid and liquid tumour types, and while causality has yet to be established, progressively more data are emerging to suggest this phenomenon may contribute to tumour growth and metastatic capacity. Herein we discuss its potential utility as a diagnostic tool and therapeutic target in light of the current in vitro, in vivo and clinical evidence linking HERV-K (HML-2) to tumour progression.